2005
DOI: 10.1002/hc.20168
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐free alkali and alkaline earth metal complexes of di‐imine ligands

Abstract: Compound [(dph-BIAN)Mg(THF)] 2 (2)was prepared by reacting magnesium metal with 1,2-bis [(2-biphenyl)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 17 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…However, the solvent-free bis(Ar-BIAN) complexes [(dipp-BIAN 47 although in the case of the former, the dipp-BIAN ligands are present as di-anions rather than mono-anions. 46 The reactivity of compound 8 toward a wide range of organic and inorganic substrates has also been examined. For example, the reduction of Ph 2 CO with 8 affords the structurally characterized pinacolate complex [{(dipp-BIAN)Mg(THF)} 2 {m-O 2 C 2 Ph 4 }] via single electron transfer (SET), in contrast to the 1,3-dipolar cycloaddition product obtained when Ph 2 CO is treated with dianionic [(R-DAB)M] complexes (M = Group 4 or lanthanide metal).…”
Section: Scheme 9 Group 1 and Group 2 Ar-bian Complexesmentioning
confidence: 99%
“…However, the solvent-free bis(Ar-BIAN) complexes [(dipp-BIAN 47 although in the case of the former, the dipp-BIAN ligands are present as di-anions rather than mono-anions. 46 The reactivity of compound 8 toward a wide range of organic and inorganic substrates has also been examined. For example, the reduction of Ph 2 CO with 8 affords the structurally characterized pinacolate complex [{(dipp-BIAN)Mg(THF)} 2 {m-O 2 C 2 Ph 4 }] via single electron transfer (SET), in contrast to the 1,3-dipolar cycloaddition product obtained when Ph 2 CO is treated with dianionic [(R-DAB)M] complexes (M = Group 4 or lanthanide metal).…”
Section: Scheme 9 Group 1 and Group 2 Ar-bian Complexesmentioning
confidence: 99%
“…As an alternative to the aforementioned low-valent alkaline earth complexes, which contain a highly reactive formally reduced metal center, substantial progress has been achieved in the study of alkaline earth complexes containing redox non-innocent ligands including α-diimines ,, and azobenzene . The use of redox active proxy ligands allows the metal center to maintain its strongly preferred 2+ oxidation state while allowing facile, reversible electron transfers at the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium complexes containing reduced diimines such as 1,2-bis­[(2,6-diisopropylphenyl)­imino]­acenaphthene ( Dipp BIAN) and 1,4-diazabutadienes have been the subjects of a number of investigations. , Yang et al reported that one- and two-electron reductions of various N,N -diaryldiazabutadienes followed by reaction with MgCl 2 gave highly varied magnesium-diimine complexes depending on the ligand steric demand and reagent stoichiometry . Among the isolated products was the Mg–Mg bonded species K 2 [(L iPr )­MgMg­(L iPr )] (L iPr = [(2,6- i Pr 2 C 6 H 3 )­NC­(Me)] 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations